2011
DOI: 10.1007/s00406-011-0235-1
|View full text |Cite
|
Sign up to set email alerts
|

The schizophrenia risk gene ZNF804A influences the antipsychotic response of positive schizophrenia symptoms

Abstract: Genetic factors determining the response to antipsychotic treatment in schizophrenia are poorly understood. A new schizophrenia susceptibility gene, the zinc-finger gene ZNF804A, has recently been identified. To assess the pharmacogenetic importance of this gene, we treated 144 schizophrenia patients and assessed the response of positive and negative symptoms by PANSS. Patients homozygous for the ZNF804A risk allele for schizophrenia (rs1344706 AA) showed poorer improvement of positive symptoms (7.35 ± 0.46) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 17 publications
2
12
0
2
Order By: Relevance
“…Zhang et al reported that Chinese T allele carriers showed significantly less symptom improvement, using the PANSS scale, while being treated with various SGAs (82). In contrast, Mö ssner et al reported that those individuals of European descent who were homozygous for the A allele showed significantly less symptom improvement in positive symptoms, based on the PANSS scale (81).…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Zhang et al reported that Chinese T allele carriers showed significantly less symptom improvement, using the PANSS scale, while being treated with various SGAs (82). In contrast, Mö ssner et al reported that those individuals of European descent who were homozygous for the A allele showed significantly less symptom improvement in positive symptoms, based on the PANSS scale (81).…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…However, several clues have emerged through cognitive studies by which this variant is associated with functional connectivity of the dorsolateral prefrontal cortex, both across hemispheres and with the hippocampus, can increase functional connectivity of the amygdala with the regulatory limbic and prefrontal areas and neuropsychological performance, such as visual memory, episodic and working memory, and attention. Consequently, these functions are impaired in patients with schizophrenia as well as bipolar disorders (Esslinger et al, 2009(Esslinger et al, , 2011Donohoe et al, 2010;Hashimoto et al, 2010;Walters et al, 2010;Balog et al, 2011;Steinberg et al, 2011;Walter et al, 2011;Kuswanto et al, 2012;Mö ssner et al, 2012). It has been recently shown that the ZNF804A gene alters expression of genes involved in cell adhesion (Hill et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Though these viewpoints are supported elsewhere [Walters et al, ; Chen et al, ], most other evidence has implicated rs1344706(A) in neurobiological deficits or severity of mental illness [Hashimoto et al, ; Balog et al, ; Voineskos et al, ; Walter et al, ; Kuswanto et al, ; Wassink et al, ; Paulus et al, ]. From a pharmacotherapeutic standpoint, SZ patients homozygous for the risk allele at rs1344706 exhibited reduced improvement of positive symptoms during antipsychotic treatment compared to patients heterozygous for rs1344706(A) [Mössner et al, ]. These findings suggest a risk‐conferring effect of rs1344706(A) and/or a role in clinical severity of SZ.…”
Section: Literature Reviewmentioning
confidence: 90%